Exome sequencing reveals novel causes as well as new candidate genes for human globozoospermia - Oud, M S; Okutman, Ö; Hendricks, L A J; de Vries, P F; Houston, B J; Vissers, L E L M; O’Bryan, M K; Ramos, L; Chemes, H E; Viville, S; Veltman, J A (Human reproduction (Oxford), 2020)
Abstract STUDY QUESTION Can exome sequencing identify new genetic causes of globozoospermia? SUMMARY ANSWER Exome sequencing in 15 cases of unexplained globozoospermia revealed deleterious mutations in seven new genes, of which two have been validated as causing globozoospermia when knocked out in mouse models. WHAT IS KNOWN ALREADY Globozoospermia is a rare form of male infertility characterised by round-headed sperm and malformation of the acrosome. Although pathogenic variants in DPY19L2 and SPATA16 are known causes of globozoospermia and explain up to 70% of all cases, genetic causality remains unexplained in the remaining patients. STUDY DESIGN, SIZE, DURATION After pre-screening 16 men for mutations in known globozoospermia genes DPY19L2 and SPATA16, exome sequencing was performed in 15 males with globozoospermia or acrosomal hypoplasia of unknown aetiology. PARTICIPANTS/MATERIALS, SETTING, METHOD Targeted next-generation sequencing and Sanger sequencing was performed for all 16 patients to screen for single-nucleotide variants and copy number variations in DPY19L2 and SPATA16. After exclusion of one patient with DPY19L2 mutations, we performed exome sequencing for the 15 remaining subjects. We prioritised recessive and X-linked protein-altering variants with an allele frequency of <0.5% in the population database GnomAD in genes with an enhanced expression in the testis. All identified candidate variants were confirmed in patients and, where possible, in family members using Sanger sequencing. Ultrastructural examination of semen from one of the patients allowed for a precise phenotypic characterisation of abnormal spermatozoa. MAIN RESULTS AND ROLE OF CHANCE After prioritisation and validation, we identified possibly causative variants in eight of 15 patients investigated by exome sequencing. The analysis revealed homozygous nonsense mutations in ZPBP and CCDC62 in two unrelated patients, as well as rare missense mutations in C2CD6 (also known as ALS2CR11), CCIN, C7orf61 and DHNA17 and a frameshift mutation in GGN in six other patients. All variants identified through exome sequencing, except for the variants in DNAH17, were located in a region of homozygosity. Familial segregation of the nonsense variant in ZPBP revealed two fertile brothers and the patient’s mother to be heterozygous carriers. Paternal DNA was unavailable. Immunohistochemistry confirmed that ZPBP localises to the acrosome in human spermatozoa. Ultrastructural analysis of spermatozoa in the patient with the C7orf61 mutation revealed a mixture of round heads with no acrosomes (globozoospermia) and ovoid or irregular heads with small acrosomes frequently detached from the sperm head (acrosomal hypoplasia). LIMITATIONS, REASONS FOR CAUTION Stringent filtering criteria were used in the exome data analysis which could result in possible pathogenic variants remaining undetected. Additionally, functional follow-up is needed for several candidate genes to confirm the impact of these mutations on normal spermatogenesis. WIDER IMPLICATIONS OF THE FINDINGS Our study revealed an important role for mutations in ZPBP and CCDC62 in human globozoospermia as well as five new candidate genes. These findings provide a more comprehensive understanding of the genetics of male infertility and bring us closer to a complete molecular diagnosis for globozoospermia patients which would help to predict the success of reproductive treatments. STUDY FUNDING/COMPETING INTEREST(S) This study was funded by The Netherlands Organisation for Scientific Research (918–15-667); National Health and Medical Research Council of Australia (APP1120356) and the National Council for Scientific Research (CONICET), Argentina, PIP grant 11220120100279CO. The authors have nothing to disclose.